Hearing Impairment in Children with Congenital Hypothyroidism - Biswas, Rabi; Islam, Md Rafiqul (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: There is increased risk of hearing impairment in children with congenital hypothyroidism (CH). Only a few studies have explored the prevalence of hearing impairment in CH and their results vary widely. There is no data of hearing impairment in Bangladeshi children with CH. Objectives: The aim of this study was to investigate the prevalence of hearing impairment in children with CH, and its relation with age of diagnosis and the dose of thyroxine (T4) they received. Methods: This study was conducted in Paediatric Endocrinology & Metabolic Disorder Department of Dhaka Shishu (Children) Hospital from July 2014 to December 2018. Hearing evaluation of 55 children diagnosed with CH was performed with a battery of tools that included Middle ear analysis, Pure Tone Audiometry (PTA), Behavioral Observation Audiometry (BOA) and Oto Acoustic Emissions (OAE). The choice of assessment tool was based on patient’s age. Results: The mean age at diagnosis and at inclusion into the study was 2.0±1.7 years and 3.2±2.3 years respectively. The etiological diagnosis was thyroid agenesis in 40(72.7%), ectopia in 3(5.5%), dyshormonogenesis in 7(12.7%) and hypothyroidism with eutopic gland in 5(9.1%%) patients. Middle ear analysis, PTA, BOA and OAE was done in 35, 28, 32 and 37 patients respectively. Sensorineural hearing loss was detected in 1 out of 55(1.8%) patients while conductive hearing loss was found in 3(5.4%) patients. Conclusion: Hearing loss was present in a small proportion of patients with permanent CH. Further larger studies are required to determine the exact prevalence of hearing impairment in Bangladeshi children with CH. DS (Child) H J 2020; 36(1) : 14-19